Features of the definition of small and pleasure vessels Ukraine’s law - Klyuyeva, Y.N. (Bulletin of the Karaganda University “Law Series”, 2020)
The purpose of the article is to analyze the current legislation of Ukraine and international normative legal acts in the field of sea and river navigation, namely, to analyze the definition of the concepts of a ship, small boat, pleasure boat. The use of the comparative legal method made it possible to carry out a comparative analysis of the norms of the current legislation of Ukraine, as well as the norms of foreign regulatory legal acts. As a result of the analysis, the author concluded that there is a variety of definitions, or rather criteria, by which a vehicle is classified as a small vessel, a small vessel, or a pleasure boat. Based on an analysis of the current national legislation, a number of laws and by-laws of ministries and departments that are related to the activities of water transport, the author made a conclusion about the discrepancy and contradiction of definitions to each other. The author emphasizes the need to bring national legislation to international and European standards. There is a need to pay attention to the legal regime of water transport in the field of registration of the considered categories of vessels. It is emphasized that in this area it is necessary to attract additional specialists in the field of sea and river navigation and further improve the national legislation in the field of registration and further use of ships of the sea and river fleet. There is a need to pay attention to the legal regime of water transport in the field of registration of the considered categories of vessels. It is emphasized that in this area it is necessary to attract additional specialists in the field of sea and river navigation and further improve the national legislation in the field of registration and further use of ships of the sea and river fleet. There is a need to pay attention to the legal regime of water transport in the field of registration of the considered categories of vessels. It is emphasized that in this area it is necessary to attract additional specialists in the field of sea and river navigation and further improve the national legislation in the field of registration and further use of ships of the sea and river fleet